A Computation Complexity Reduction of the Size Decision Algorithm in 3D-HEVC Depth Map Intracoding. (29th June 2022) - Hamout, Hamza; Elyousfi, Abderrahmane
Abstract : A new video format called a multiview video plus depth map is recently designed as the most efficient 3D video representation. 3D-high efficiency video coding (3D-HEVC) is the international standard for 3D video coding finalized in 2016. In 3D-HEVC intracoding, the depth map is an essential component, in which the depth map intraprediction occupies more than 85% of the overall intraencoding time. In 3D-HEVC design, a highly flexible quadtree coding unit partitioning is adopted, in which one coding tree unit is partitioned recursively into a prediction unit (PU) from 64 × 64 down to 4 × 4. This highly flexible partitioning provides more accurate prediction signals and thereby achieves better intradepth map compression efficiency. However, performing all depth map intraprediction modes for each PU level achieves high depth map intracoding efficiency, but it results in a substantial computational complexity increase. This paper proposes an amelioration of the previously proposed depth map PU size decision using an efficient homogeneity determination. The resulting experiences show that the proposed method can significantly save the computational complexity with a negligible loss of intracoding efficiency.